In vitro Antimicrobial Activity of Fosfomycin, Rifampin, Vancomycin, Daptomycin Alone and in Combination Against Vancomycin-Resistant Enterococci - Tong J; Jiang Y; Xu H; Jin X; Zhang L; Ying S; Yu W; Qiu Y (Dove Medical Press, 2021)
Jiepeng Tong,1 Yiheng Jiang,2 Hao Xu,1 Xuehang Jin,1 Li Zhang,1 Shuaibing Ying,1 Wei Yu,1 Yunqing Qiu1 1State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, Zhejiang Provincial Key Laboratory for Drug Clinical Research and Evaluation, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People's Republic of China; 2Clinical Medicine, Nanjing Medical University, Nanjing, People's Republic of ChinaCorrespondence: Wei Yu; Yunqing Qiu Email wyu@zju.edu.cn; qiuyq@zju.edu.cnPurpose: The emergence of vancomycin resistant Enterococci (VRE) is shortening the choices for clinical anti-infective therapy. The aim of this study was to investigate the mechanism of vancomycin resistance and evaluate the effect of fosfomycin (FM), rifampin (RIF), vancomycin (VAN), linezolid (LNZ), daptomycin (DAP) alone or in combination against VRE.Methods: Eight VRE isolates were collected. A total of 18 antibiotics susceptibility tests were further done for VRE. Whole genome sequencing and bioinformatics analysis were performed. The effect of FM, RIF, VNA, LNZ, DAP alone or in combination was determined using anti-biofilm testing and the time-kill assay.Results: All isolates were susceptible to LNZ and DPA. The high-level resistance determinant of VAN in these strains was due to VanA-type cassette. MLST revealed two different STs for vancomycin-resistant Enterococcus faecium (VREm) and four different STs for vancomycin-resistant E. faecalis (VREs). Virulence genes in VREs were more than VREm, especially for 4942 isolated from blood. Gene acm and uppS were only identified in VREm, while virulence genes related to cytolysin were only found in E. faecalis. Further in vitro studies indicated FM (83 mg/L) combined with DAP (20.6 mg/L) and DAP monotherapy (47.1 mg/L) had bactericidal effect against VRE isolates at 24h.Conclusion: High-level resistance determinant of VAN in tested isolates was due to VanA-type cassette. FM combined with DAP is a potential therapeutic option for VRE infections.Keywords: vancomycin, daptomycin, combination therapy, biofilm